LEAN ACCOUNTING: SUATU ALTERNATIF TEKNIK AKUNTANSI MANAJEMEN DALAM INDUSTRI MANUFAKTUR - Ardhani Sisdyani, Eka (Jurnal Ilmiah Akuntansi dan Bisnis, 2010)
Manufacturing techniques have been developed to embrace theaims of continuous improvement. Continuous improvement would leadcompanies to win business competition. One technique that gains moreand more followers is lean manufacturing. Lean manufacturing hastwo main purposes, which are eliminating wastes and creating valuesto customers. It focuses on customer values, value stream, productionflows, demand-pull, and perfection. Lean accounting is needed tosupport and encourage the development of lean manufacturing, forinstances in product costing system, external reporting, and otherdecision making processes that need accounting data.
Keywords: lean manufacturing, lean accounting, value stream.